Asociación entre el polimorfismo genético de la apolipoproteína E (ApoE) y la enfermedad de Parkinson - Marca, Victoria (2013)
Due to the increase in life expectancy in our country, it is necessary to study risk factors for Parkinson’s disease (PD), including apolipoprotein E (ApoE) gene, as this association is not known in our country. Objectives: To determine association of ApoE gene polymorphism and PD. Design: Associative, observational case-control analytic study. Setting: Instituto Nacional de Ciencias Neurologicas, Lima, Peru. Participants: Male and females with and without Parkinson's disease. Interventions: Genomic DNA was extracted from 163 patients and 176 controls. PCR_RFLP technique was used for ApoE gene genotyping. Main outcome measures: ApoE gene genotype and allele frequencies in cases and controls, association and risk. Results: No significant ApoE genotype differences between the control group and patients were found. Allele ε4 frequency was similar in patients and controls: 6.5 and 6.0. Odds ratio for ApoE ε4 allele associated with PD was 1.2163 (IC 95%, 0.6574-2.2507). Conclusions: ApoE ε4 allele could not be considered a risk factor for PD in the population studied.